Operations excellence management system (OEMS) : getting it right the first time /: getting it right the first time. (2019) - Lutchman, Chitram; Lutchman, Kevan; Akula, Ramakrishna; Lyons, Charles; Al Hashmi, Waddah S. Ghanem
No abstract available